AN Overview Of Musculoskeletal Disorders ConditionsAt The Leather Wallet Craftsman At UD. Nanan - Putri, Fadma; Wicaksono, Utomo; Abdullah, Khabib; Siwi, Ken; Alif Amalia, Dinda (FISIO MU: Physiotherapy Evidences, 2023)
Introduction: The characteristic of working conditions for leather craftsmen is sitting cross-legged with a cushion in front of the work table. This job is a job with low mobility. Such working conditions can trigger occupational diseases such as muscle complaints which are commonly known as musculoskeletal disorders (MSDs). Purpose: to find out musculoskeletal complaints experienced by craftsmen before and after work. Methods: This research uses an evaluative research design with a sample of 30 people. Data was obtained by interviews and using the Nordic Body Map questionnaire to measure musculoskeletal complaints before and after work. Data before and after work from variables were statistically analyzed with SPSS version 26.0. Results: The results of data analysis showed that there was a significant increase in musculoskeletal complaints before and after work, p = 0.00. Conclusion: musculoskeletal complaints increased by 25.45% after undergoing work processes that were not ergonomic or without considering the capacity of the worker